Kedudukan Hukum Dropshipper dalam Transaksi Jual Beli Online - Belinda Dwi Tamara (Faculty of Law, Universitas Airlangga, 2021)
AbstractNowadays, online buying and selling transactions are becoming a trend for running a digital business. In marketing a product in the digital world, the role of a trade intermediary is needed to bridge the spread of information and / or specifications for a product widely from various groups, namely the dropship system. The existence of the dropshipper creates a legal relationship between the parties, namely the dropshipper with the seller and the dropshipper with the buyer. If the dropshipper manages to get a prospective buyer, the dropshipper orders the prospective buyer order from the supplier of the goods. It is the supplier of the goods who sends the product to the buyer on behalf of the dropshipper. Thus, it creates a legal position for the dropshipper and the dropshipper's accountability in the online buying and selling transaction process.Keywords: The Dropshipping System; Online Buying and Selling Transaction; Responsibility; Intermediary Traders.AbstrakSaat ini, transaksi jual beli online menjadi suatu trend untuk menjalankan suatu bisnis digital. Dalam pemasaran suatu produk didunia digital diperlukan peran perantara dagang guna menjembatani penyebaran informasi dan/atau spesifikasi suatu produk secara luas dari berbagai kalangan yaitu sistem dropship. Adanya dropshipper tersebut menimbulkan suatu hubungan hukum antar para pihak yaitu dropshipper dengan penjual dan dropshipper dengan pembeli. Jika pihak dropshipper berhasil mendapatkan calon pembeli, maka pihak dropshipper memesankan pesanan calon pembeli kepada supplier barang. Supplier baranglah yang mengirimkan produk tersebut kepada pembeli dengan atas nama pihak dropshipper. Dengan demikian, menimbulkan suatu kedudukan hukum bagi dropshipper dan tanggung gugat dropshipper dalam dari proses transaksi jual beli online. Kata Kunci: Sistem Dropship; Transaksi Jual Beli Online; Tanggung Gugat; Perantara Dagang.